Ehrhart theory of lattice path matroid polytopes (2021)
We study h*-vectors of lattice path matroids polytopes. Since these polytopes are alcoved, as a first step, we provide a combinatorial toolkit for the analysis of such vectors of this larger family. Based on this, we obtain a combinatorial interpretation of the h*-vector of lattice path matroids of rank 2. This yields formulas for the h*-vector and the volume of such matroid polytopes. Furthermore, we characterize Gorenstein lattice path matroids.